Utbildningsplattform för omvårdnadspersonal som behöver ökad kunskap om Parkinsons sjukdom - Ingerslev,Julia; Gustafsson,Jacob (2025)
This project introduces the development of a digital educational platform designed to strengthen knowledge and awareness of Parkinson’s disease among healthcare personnel, particularly within home care and nursing services. The initiative stems from a recognized need for accessible and disease-specific information, as new employees often do not receive the training and knowledge needed to provide optimal care for people with Parkinson's disease. The platform provides medical information formulated in comprehensible language, specifically tailored for non-specialist caregivers. The content is divided into four main and several subchapters, each supplemented by interactive quizzes to encourage active learning and knowledge retention. Video material is integrated, further supporting different learning preferences and enhancing engagement. The website is intended for everyday use, allowing staff to retrieve relevant information when needed. The project was conducted in Lund, and the evaluation of the website was carried out with multiple healthcare professionals at the Billingshäll nursing home in Kävlinge. The evaluation indicated that the proposed solution was well received and was considered beneficial in achieving a higher and more standardized level of competence in the care of individuals with Parkinson's disease. Using intuitive design and concise information, this project addresses a critical gap in caregiver knowledge. It shows how digital solutions can support the development of competences and contribute to more informed, confident, and consistent care for people living with Parkinson's disease.
Keywords: Parkinsons sjukdom; utbildningsplattform; omvårdnadspersonal